1978
DOI: 10.1111/j.1432-1033.1978.tb12212.x
|View full text |Cite
|
Sign up to set email alerts
|

Membrane Lipid Metabolism in Acholeplasma laidlawii A EF 22

Abstract: 1. Membrane lipid metabolism in Acholeplasma laidlawii A EF 22 has been studied under different conditions by applying three different techniques for changing membrane viscosity : fatty acid and cholesterol supplementation and temperature changes.2. The molar relationship between the two dominating membrane lipids, monoglucosyldiglyceride and diglucosyldiglyceride, is to a large extent determined by membrane viscosity properties. This is shown by the varying metabolic responses occurring during incorporation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

1981
1981
1993
1993

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(27 citation statements)
references
References 36 publications
0
27
0
Order By: Relevance
“…Since MGDG is the only lipid that alone with water can form nonlamellar phase structures, it is a key component in determining the phase equilibria of the in vivo mixtures. The ratio MGDG/DGDG in the A. laidlawii membrane is extensively regulated upon alterations of the growth conditions (Wieslander & Rilfors, 1977;Christiansson & Wieslander, 1978, 1980; Christiansson et al, 1981;Rilfors, 1985;Clementz et al, 1986). The regulations can be explained by the phase equilibria in MGDG-water, MGDG-DGDG-water, and in vivo total polar lipid-water mixtures, and hence by the ideas of lipid molecular geometry (Wieslander et al, 1980(Wieslander et al, , 1981aRilfors, 1985;Lindblom et al, 1986).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since MGDG is the only lipid that alone with water can form nonlamellar phase structures, it is a key component in determining the phase equilibria of the in vivo mixtures. The ratio MGDG/DGDG in the A. laidlawii membrane is extensively regulated upon alterations of the growth conditions (Wieslander & Rilfors, 1977;Christiansson & Wieslander, 1978, 1980; Christiansson et al, 1981;Rilfors, 1985;Clementz et al, 1986). The regulations can be explained by the phase equilibria in MGDG-water, MGDG-DGDG-water, and in vivo total polar lipid-water mixtures, and hence by the ideas of lipid molecular geometry (Wieslander et al, 1980(Wieslander et al, , 1981aRilfors, 1985;Lindblom et al, 1986).…”
Section: Resultsmentioning
confidence: 99%
“…The membrane lipid composition in Acholeplasma laidlawii is regulated in response to changes of several environmental conditions. The conditions chosen in previous investigations were mainly of the kind that the organism will meet in its biological surroundings, such as changes in the growth temperature and the presence of cholesterol and different fatty acids used in membrane lipid synthesis (Wieslander & Rilfors, 1977;Christiansson & Wieslander, 1978, 1980Rilfors, 1985). One important aim of this regulation is to maintain a stable lipid bilayer structure during various environmental conditions (Wieslander et al, 1980(Wieslander et al, , 1981aRilfors et al, 1984;Rilfors, 1985).…”
Section: Discussionmentioning
confidence: 99%
“…To obtain lipids containing only cis-unsaturated acyl chains, the growth medium was supplemented with 150 µ oleic acid (Wies- lander & Rilfors, 1977; and the cells were harvested after growth for 36 h at 30 °C. This temperature has the effect of increasing the relatively low amounts of MGDG normally obtained with oleic acid supplementation (Christiansson & Wieslander, 1978). Lipids containing approximately equal amounts of an unsaturated and a saturated acyl chain were obtained by supplementing the medium with 75 µ oleic acid and 75 µ palmitic acid and growing the cells for 24 h at 37 °C (Wieslander & Rilfors, 1977;.…”
Section: Methodsmentioning
confidence: 99%
“…Little was known about the membrane phospholipids of M. hyopneumoniae. The results showed that PG and DPG were the major phospholipids in membrane of mycoplasma cells except A. iaidfawii where glycophospholipids were also found [13]. Only M. hominis (ATCC 15056) contained PG, phosphatidic acid (PA) and lysophosphatidylglycerol (LPG) [14].…”
Section: Resultsmentioning
confidence: 99%